The Menuju Desa Mandiri: Peningkatan Kapasitas UMKM di Desa Mekarsari melalui Pelatihan Fundamental Bisnis - Fitriani, Nur Laila; Fauziyah, Syifa Nur; Vallma, Calysta; Rafi, Faisa; Hanifatun, Diyas; Hidayati, Fatma; Husnaa, Alifya Nabilla; Almunawar, Muhammad Ihsan; Nindyantoro, Nindyantoro (Jurnal Pusat Inovasi Masyarakat, 2024)
The development of technology and digitalization has driven significant transformation in the Micro, Small and Medium Enterprises (MSMEs) sector in Indonesia. In Mekarsari Village, Bandung Regency, MSMEs face various challenges, especially in financial management, marketing, and product packaging. The program “Be Fun for U: Business Fundamental for MSMEs” initiated by the IPB Innovation KKN-T Team aims to strengthen business management in Mekarsari Village MSMEs to focus on four management pillars including financial management, marketing, human resources (HR), and supply chain. The training was held on July 6, 2024 at Mekarsari Village Hall, involving 17 MSME players representing various business sectors. Findings from the training showed that while some MSMEs have adopted digital marketing, key issues such as unstructured financial management and lack of brand identity are still significant. Solutions introduced included the use of Lamikro app for financial record keeping, logo creation for branding, and assistance in the halal certification process as well as Business Identification Number (NIB) registration. The program successfully improved MSMEs' understanding of business management and provided practical solutions to the constraints faced. This success is expected to strengthen MSME competitiveness and support sustainable economic growth in Mekarsari Village.